2016
DOI: 10.1021/acs.chemrev.6b00144
|View full text |Cite
|
Sign up to set email alerts
|

Hexaarylbenzene: Evolution of Properties and Applications of Multitalented Scaffold

Abstract: The easily rotatable peripheral aromatic rings around central benzene in hexaarylbenzene (HAB) derivatives create a very intriguing nonplanar, propeller-shaped geometry. Because of the very low susceptibility toward self-aggregation, HAB derivatives are much stronger candidates among various polyphenylenes/hetero-oligophenylenes when poor molecular cohesion and inefficient packing is required. However, the native properties of hexaphenylbenzene (HPB) can be varied by proper tailoring and substitution of the HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 295 publications
3
74
0
Order By: Relevance
“…Nevertheless, it is interesting to note that all aryl substituents, including the thienyl group on boron, are arranged in a propeller‐like fashion around the central ring, indicating no significant conjugation between them . A striking aspect of the molecular structure of 11 is the nearly perpendicular orientation of the aryl ring substituents relative to the central azaborinine, which is in stark contrast to the commonly observed preference for a propeller‐like arrangement enabling π–π interactions between all of the aromatic groups at the periphery (see Figure S5 in the Supporting Information) . The observed change in conformation is most likely due to the differently polarized π system of the pentafluorophenyl group disrupting the toroidal conjugation …”
Section: Resultsmentioning
confidence: 85%
“…Nevertheless, it is interesting to note that all aryl substituents, including the thienyl group on boron, are arranged in a propeller‐like fashion around the central ring, indicating no significant conjugation between them . A striking aspect of the molecular structure of 11 is the nearly perpendicular orientation of the aryl ring substituents relative to the central azaborinine, which is in stark contrast to the commonly observed preference for a propeller‐like arrangement enabling π–π interactions between all of the aromatic groups at the periphery (see Figure S5 in the Supporting Information) . The observed change in conformation is most likely due to the differently polarized π system of the pentafluorophenyl group disrupting the toroidal conjugation …”
Section: Resultsmentioning
confidence: 85%
“…[45] a) Ph 2 O, 260 8C, mW; b) Ni(acac) 2 ,toluene, 110 8C; c) Co 2 (CO) 8 [31] was synthesized in al iterature-known statistical porphyrin condensation and reactedw ith tetracyclone 2 [40,42] to the mono-porphyrin-HPB 3. [31,38] The transformation to the respective HBC derivative 6 workeda lmost quantitatively using FeCl 3 as the oxidant. To lane-porphyrin 1 is further suitable for the preparation of tri-porphyrin-substituted HPBs.…”
Section: Resultsmentioning
confidence: 99%
“…Hexaphenylbenzenes (HPBs) and their oxidized derivatives hexa‐ peri ‐hexabenzocoronenes (HBCs) have received tremendous attention during the past 20 years in materials chemistry, for example in molecular electronics and nonlinear optics . They have proven to be a suitable scaffold for catalytic applications, the design of supramolecular architectures, as well as a perfectly sized template for the preparation of nano‐ring and nano‐ball structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel methods to improve the preparation of functionalized multiarenes for these applications are continuously being sought. Reflecting the importance of developing new methods to access novel polyaryl systems, Suzuki et al ( 32 ) have recently reported the elegant synthesis of a new class of “multitalented” hexaarylbenzenes ( 33 ) that contain five or six different arene substituents on a single benzene molecule.…”
Section: Introductionmentioning
confidence: 99%